Expanding the Margins: High Volume Utilization of Marginal Liver Grafts Among >2000 Liver Transplants at a Single Institution. Issue 3 (September 2017) - Halazun, Karim J.; Quillin, Ralph C.; Rosenblatt, Russel; Bongu, Advaith; Griesemer, Adam D.; Kato, Tomoaki; Smith, Craig; Michelassi, Fabrizio; Guarrera, James V.; Samstein, Benjamin; Brown, Robert S.; Emond, Jean C.
Abstract : Objective: Marginal livers (ML) have been used to expand the donor pool. National utilization of MLs is variable, and in some centers, they are never used. We examined the outcomes of MLs in the largest single center series of MLs used to date and compared outcomes to standard (SL) and living donor (LD) livers. Methods: Analysis of a prospectively maintained database of all liver transplants performed at our institution from 1998 to 2016. ML grafts were defined as livers from donors >70, livers discarded regionally and shared nationally, livers with cold ischemic time >12 hours, livers from hepatitis C virus positive donors, livers from donation after cardiac death donors, livers with >30% steatosis, and livers split between 2 recipients. Results: A total of 2050 liver transplant recipients were studied, of these 960 (46.8%) received ML grafts. ML recipients were more likely to have lower MELDs and have hepatocellular carcinoma. Most MLs used were from organs turned down regionally and shared nationally (69%) or donors >70 (22%). Survival of patients receiving MLs did not significantly differ from patients receiving SL grafts ( P = 0.08). ML and SL recipients had worse survival than LDs ( P < 0.01). Despite nearly half of our recipients receiving MLs, overall survival was significantly better than national survival over the same time period ( P = 0.04). Waitlist mortality was significantly lower in our series compared with national results (19% vs 24.0%, P < 0.0001). Conclusions: Outcomes of recipients of ML grafts are comparable to SL transplants. Despite liberal use of these grafts, we have been able to successfully reduce waitlist mortality while exceeding national post-transplant survival metrics.